Organosulfur compounds in ambient fine particulate matter in an urban region: Findings of a nontargeted approach - Li, Ailin; Shi, Xiaodi; Xinghua Qiu; Wei, Gaoyuan; Yan Zheng; Chen, Qi; Shiyi Chen; Min Hu; Zhu, Tong (Science of The Total Environment, 2023)
Organosulfur compounds (OSCs) are important components of fine particulate matter (PM2.5); however, little information is available on OSCs in urban regions due to their chemical complexity, especially for novel species such as aromatic sulfonates. To supplement the detection technique and systematically identify OSCs, in this study we developed a nontargeted approach based on gas chromatography and high-resolution mass spectrometry (GC-HRMS) to screen OSCs in PM2.5 of urban Beijing and provide field evidence for their source and formation mechanism. 76 OSCs were found through mass difference of sulfur isotopes and characteristic sulfur-containing fragments. 6 species were confirmed as aromatic sulfonates by authentic standards. 32 OSCs showed higher levels in the heating season, presumably because of the intensive emission, especially from coal combustion. While certain species, with 2-sulfobenzoic acid as the representative, were 2.6-times higher in the non-heating season than in the heating season. Such species were significantly correlated with ozone and aerosol liquid water content (r = 0.2–0.8, p < 0.05), implying an oxidation-involved aqueous-phase formation in the atmosphere. In addition, with an average proportion of ∼95 % of the total sulfobenzoic acids, the predominance of the 2-substitution product over its isomers of 3- or 4-sulfobenzoic acid suggests a more plausible mechanism of radical-initiated reaction of phthalic acid followed by sulfonation, with atmospheric reactivity indicated by ozone and temperature as the determining factor. This study provided not only a nontargeted approach for OSCs in ambient PM2.5, but also field evidence on their secondary formation proposed in previous simulation studies.